Trade-off between coherence and heat in a non-Markovian dephasing dynamics - Lenzarini, Marino Paiva (2026)
The relation between quantum coherence and thermodynamic irreversibility is of fundamental importance for understanding the concepts of quantum thermodynamics. In this work, we investigate this connection within the pure dephasing framework, in which a central qubit interacts with a finite spin environment modeled as an Ising chain. Although no net energy exchange occurs between the system and the environment, the qubit undergoes decoherence, revealing nontrivial thermodynamic behavior. The dynamics of coherence are analyzed numerically through the magnitude of the time-dependent coherence function ⌈(t), whose oscillatory behavior provides evidence of information backflow and non-Markovian features. By computing the Breuer−Laine−Piilo measure, we confirm that the information flux becomes positive during coherence revivals, signaling memory effects arising from the finite environment. From a thermodynamic perspective, the numerical results demonstrate that the mean heat and the work evolve in perfect antiphase, satisfying the energetic balance relation ⟨Q⟩ = ⟨W⟩. Moreover, the mean heat ⟨Q⟩ and |⌈(t)| exhibit intertwined behavior: the maximum of heat dissipation occurs when coherence reaches its minimum, indicating a trade-off in the pure dephasing regime. This behavior shows that heat dissipation in this regime acts as a thermodynamic signature of coherence loss and recovery.